THE RELEVANCE OF THE EFFECT OF IRON DEFICIENCY ANEMIA DURING PREGNANCY ON THE HEALTH OF THE CHILD - Kaldarova, Aigerim (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2024)
The main goal of the article is to prevent neglect of the health of women and children during pregnancy. Among a number of diseases, iron deficiency anemia is very important, because it does not only affect the health of the mother, but also prevents the formation and growth of organs and systems of the fetus in the womb. The reason for choosing the following topic is that many studies on the topic of iron deficiency anemia have been published by domestic and foreign authors. That is, how much iron deficiency anemia affects the health of the expectant mother and unborn child, the relevance of this topic in the field of medicine and other fields beyond its borders. The article includes studies and scientific papers on iron deficiency anemia, as well as unique results on the topic. The study included 10 newborns born to mothers diagnosed with anemia during pregnancy. The condition of newborn was assessed as severe and moderate. Long-term respiratory diseases and changes in the nervous system were noted. Received treatment according to the protocol of diagnosis and treatment in accordance with clinical diagnoses. On the basis of the conducted research, it was concluded that it is necessary to reduce the percentage of iron deficiency anemia among pregnant women and children